Mindfulness for adaptation to analog and new technologies emergence for long-term space missions - Le Roy, Barbara; Martin-Krumm, Charles; Trousselard, Marion (Frontiers in Space Technologies, 2023)
Long-term space missions require a good understanding of human adaptation to space hostile environments. Some professional environments share isolated and/or confined and/or extreme and/or unusual constraints with space. They can provide space analogs for studying challenge adaptation as their environmental constraints disrupt the balance between the demands of the environment and the resources mobilized by individuals. This impairs in homeostasis leads to increase stress, decrease performances, and the overall health of these professionals. Nevertheless, as analogs, these professional environments can also offer information for better identifying the individual psychological and cognitive resources that are effective in adaptation with the constraints caused by these exceptional environments. Studies suggest that a relevant candidate for dealing with them might be the mindfulness functioning (i.e., awareness that emerges by paying attention purposefully, in the present moment, without judgment to the experience that is unfolding moment by moment). Thus, we address the mindfulness functioning as being a relevant psychological resource to face the constraints of space missions based on mindfulness experiences from analog environments and military contexts. We propose to open discussions on new countermeasures focused on developing mindfulness, especially using new technologies (e.g. "immersive reality", and others), to increase adaptation to space environment and offer programs tailored to the needs of astronauts for long space journeys.